Electrochemical Characteristics Based on Skin-Electrode Contact Pressure for Dry Biomedical Electrodes and the Application to Wearable ECG Signal Acquisition. (16th September 2021) - Song, Jinzhong; Zhou, Tianshu; Liang, Zhonggang; Liu, Ruoxi; Guo, Jianping; Yu, Xinming; Cao, Zhongping; Yu, Chuang; Liu, Qingjun; Li, Jingsong
Abstract : Based on one simulated skin-electrode electrochemical interface, some electrochemical characteristics based on skin-electrode contact pressure (SECP) for dry biomedical electrodes were analysed and applied in this research. First, 14 electrochemical characteristics including 2 static impedance (SI) characteristics, 11 alternating current impedance (ACI) characteristics and one polarization voltage (PV), and 4 SECP characteristics were extracted in one electrochemical evaluation platform, and their correlation trends were statistically analysed. Second, dry biomedical electrode samples developed by the company and the laboratory, including textile electrodes, Apple watch, AMAZFIT rice health bracelet 1S, and stainless steel electrodes, were placed horizontally and vertically on the "skin" surface of the electrochemical evaluation platform, whose polarization voltages were quantitatively analysed. Third, electrocardiogram (ECG) collection circuits based on an impedance transformation (IT) circuit for textile electrodes were designed, and a wearable ECG acquisition device was designed, which could obtain complete ECG signals. Experimental results showed SECP characteristics for dry electrodes had good correlations with static impedance and ACI characteristics and the better correlation values among 2-10 Hz. In addition, polarization voltages in vertical state were smaller in horizontal state for dry biomedical electrodes, and polarization voltage of electrode pair (PVEP) values for Apple watch bottom was always smaller than ones for Apple watch crown and LMF-2 textile electrode. And the skin-electrode contact impedance of IT textile electrodes was less than the traditional textile electrodes.